Peran Pendidik Terhadap Pembentukan Karakter Santri di RTQ Miftahul Jannah Pontana Kecamatan Malua Enrekang - Hairul Hairul; M Yunus Sudirman (EduPsyCouns: Journal of Education, Psychology and Counseling, 2022)
Abstract: The Tahfidz Al-Qur'an House plays an important role in improving the behavior of students through the role of the Educator. The educator or ustad does not only play a role in teaching but guides, trains and advises in improving the character of the students. The purpose of this study was to determine the role of the educator in the formation of the character of the Santri at the Miftahul Jannah Pontana Tahfidz Quran House, Malua Village, Malua District, Enrekang Regency. There is a formulation of the problem, namely, what is the role of educators in the formation of the character of students at the Tahfidz Quran Miftahul Jannah Pontana House, Malua Village? The benefits of this research are theoretical and practical benefits. This research uses descriptive research with a qualitative approach. Data collection techniques are carried out by means of observation, interviews, and documentation. data processing techniques namely using research extension, increasing persistence, and triangulation using source and technique triangulation. Data analysis was performed using Miles and Huberman's model analysis, namely data collection, data reduction, data presentation, and drawing conclusions. Based on the analysis of the data that has been processed, it can be concluded that educators at the Miftahul Jannah Pontana Tahfidz Quran House, Malua Village, play an important role in shaping the character of students through mentoring, training, and advising in forming religious, independent, and communicative characters. Abstrak: Rumah Tahfidz Al-Qur'an sangat berperan penting dalam memperbaiki perilaku santri melalui peran Pedidik. Pendidik atau ustad tidak hanya berperan dalam pengajaran melainkan membimbing, melatih dan menasihati dalam meperbaiki karakter santri . Tujuan penelitian ini adalah untuk mengetahui Peran Pendidik terhadap Pembentukan Karakter Santri di Rumah Tahfidz Quran Miftahul Jannah Pontana Kelurahan Malua Kecamatan Malua Kebupaten Enrekang. Penelitian ini menggunakan jenis penelitian deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara, dan dokumentasi. teknik pengolahan data yakni menggunakan perpanjangan penelitian, peningkatan ketekunan, dan triangulasi menggunakan triangulasi sumber dan teknik. Analisis data dilakukan dengan menggunakan analisis model Miles dan Huberman yakni pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Berdasarkan analisis data yang telah diolah maka dapat disimpukan bahwa pendidik di Rumah Tahfidz Quran Miftahul Jannah Pontana Kelurahan Malua sangat berperan penting dalam membentuk karakter santri melalui pembimbingan, melatih, dan menasehati dalam membentuk karakter religius, mandiri, serta komunikatif.